This Is Not The End - Hite, Alexander. (Tufts University. Tisch Library., 2019)
This Is Not The End is the partial score for the original video game of the same name. The game is currently being developed by students from Northeastern University's Game Design program, with whom I collaborated over the course of the full academic year. In the words of creator Marri Kang, "This Is Not The End is a JRPG centered on the millennial experience with depression. The game is based on personal experiences, outlining the process of accepting mental illness and, more importantly, learning how to heal from it." This thesis is a collection of five musical themes, each written for a specific event or setting within the game. Instrumentation for the live performance included wind controller, two synthesizers, violin, cello, and drum set. In addition, footage from the game was projected onto a screen in the background.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Music.; Advisor: John McDonald.; Committee: Kareem Roustom, and Paul Lehrman.; Keyword: Musical composition.